1974
DOI: 10.1002/ajpa.1330400302
|View full text |Cite
|
Sign up to set email alerts
|

Skinfold thicknesses in a national probability sample of U.S. males and females aged 6 through 17 years

Abstract: Cycles II and III of the Health Examination Survey included measurements of the skinfolds of over 14,000 individuals 6 through 17 years of age, statistically weighted to provide an accurate national probability sample. Analyses of the triceps and subscapular skinfolds of Negroes and whites are reported here, utilizing the median in preference to the mean. Females of either racial group have thicker skinfolds at all ages studied. Whites have greater median triceps thicknesses than Negroes of the same sex and ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

1980
1980
1999
1999

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 0 publications
2
8
0
Order By: Relevance
“…It can be argued that, since the study sample was weighted by children who were either lighter or heavier than average for their age, the observed relative excess of subscapular skinfold thickness in the blacks may constitute a sampling artifact. However, in the National Health Examination Survey, the same reIationship was shown (Johnston et al, 1973(Johnston et al, , 1974b. Also, there was no statistically significant difference in triceps skinfold distribution by age between the complete Bogalusa childhood population (aged 5-14 years) and the present sample for the four race-sex groupings.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…It can be argued that, since the study sample was weighted by children who were either lighter or heavier than average for their age, the observed relative excess of subscapular skinfold thickness in the blacks may constitute a sampling artifact. However, in the National Health Examination Survey, the same reIationship was shown (Johnston et al, 1973(Johnston et al, , 1974b. Also, there was no statistically significant difference in triceps skinfold distribution by age between the complete Bogalusa childhood population (aged 5-14 years) and the present sample for the four race-sex groupings.…”
Section: Discussionsupporting
confidence: 51%
“…Earlier studies showed only slight differences between black and white children in subscapular skinfold averages in contrast to larger differences in triceps skinfold thickness (Johnston et al, 1973(Johnston et al, , 1974a. The fat layer in whites appears more uniform in thickness than is the case among blacks.…”
Section: Discussionmentioning
confidence: 94%
“…The timing of the fatness increaseldecrease is not represented by the component score. It is controversial whether the adolescent fat wave occurs on the trunk in males and at any site in females (Reynolds, 1951;Garn and Haskell, 1959;Johnston et al, 1974;Garn et al, 1981;Tanner et al, 1981). Because a similar pattern of increaseldecrease is summarized in the second component, the present analysis supports the contention that the fat wave occurs at each site and in each sex.…”
Section: Discussionsupporting
confidence: 83%
“…In fact, it has been reported that Blacks tend to store more fat centrally than peripherally (35)(36)(37). For instance, Kumanyika (23) reported that, in the NHANES II data, obese Black women have a relative excess of truncal fat compared with extremity fat, as manifested by greater differences in subscapular than triceps skin folds (23).…”
Section: Obesitymentioning
confidence: 97%